PENGARUH KUALITAS PRODUK WISATA SEJARAH TERHADAP KEPUTUSAN BERKUNJUNGDI KABUPATEN KUNINGAN : Survei pada Wisatawan Wisata Sejarah di Kabupaten Kuningan - Reffy Primayanti Marmagati, - (2010)
Gedung Perundingan Linggarjati and Taman Purbakala Cipari supposed to be the heritage tourism there is Kuningan Regency. Experience reduction way continous as follows in the year 2006 until 2009. If it happened reduction way continous, it will be worried to experienced extinction or it less knew the heritage tourism in the Kuningan Regency. Therefore it did effort for development the heritage tourism in the Kuningan Regency as it try to preserve the history remainder and it can be hoped in increasing visit tourist to the history a tour. Reduction level call on tourist to the heritage tourism in the Kuningan Regency is caused by the product monotonous that offering and less interesting call on the heritage tourism. It times now more a tourist consider quality side from attraction a tour which offered. Therefore the quality product a tour is supposed to be the thing that is important in the tourism because it can influential toward a tourist satisfaction who will impact to decision call on her/his next. The quality product a tour in this research is object quality interesting a tour, attraction quality a tour, instrument support quality a tour and acsesbilitation quality. This kind of research have the quality description and verification with using the explanatory survey method. The research of sample is amounting to 120 people a tourist with using collection sample technique systematic random sampling through cross sectional approach method and for data analyze technique which used in this research is regression linear double. The result of research declare that the quality product a tour influential in the amount of 53,5% toward decision visit to the heritage tourism in the Kuningan Regency. Based on calculation of result SPSS 18.0 be got similarity regression as follows Y = 16,180+0,420x1+0,851x2+0,285x3+0,322x4. On the whole based on trial hypothesis show the quality product a tour is quality interesting a tour, attraction quality a tour, instrument support quality a tour and acsesbilitation quality influential significant toward visiting decision to the heritage tourism in the Kuningan Regency.